Strengthening Legal Framework for Wildlife Poaching Prevention in Indonesia: Peningkatan Kerangka Hukum untuk Pencegahan Perburuan Liar Satwa Liar di Indonesia - Saxti, Muhammad Bima; Rosnawati, Emy (Indonesian Journal of Law and Economics Review, 2025)
General Background: Indonesia possesses one of the world’s richest biodiversities but faces a severe decline in wildlife populations due to poaching and illegal trade. Specific Background: The escalation of poaching activities has disrupted ecosystems and reduced protected species, demanding effective legal protection. Knowledge Gap: Previous studies focused mainly on poaching causes and enforcement issues, yet few examined the comprehensive legal urgency from Indonesia’s positive law perspective. Aims: This study analyzes the urgency of legal protection against wildlife poaching based on Indonesian positive law. Results: The findings show that existing regulations such as Law No. 5/1990 and Government Regulation No. 7/1999 provide a clear foundation for protecting endangered species but require stronger enforcement, community involvement, and synchronization among institutions. Novelty: This research emphasizes the integrative role of legal instruments in ensuring wildlife sustainability through both in situ and ex situ conservation. Implications: Strengthened law enforcement and public awareness are vital to preserving biodiversity and maintaining ecological balance. <article class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto [content-visibility:auto] supports-[content-visibility:auto]:[contain-intrinsic-size:auto_100lvh] scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" tabindex="-1" data-turn-id="de64ff8d-afdb-4d89-80eb-4a8d4ec2fd6e" data-testid="conversation-turn-2" data-scroll-anchor="false" data-turn="assistant"> <div class="[--thread-content-max-width:40rem] thread-lg:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-1" dir="auto" data-message-author-role="assistant" data-message-id="9738ae5a-8316-4b79-9169-42882fa514e4" data-message-model-slug="gpt-5"> Highlight: Emphasizes Indonesia’s legal framework for wildlife protection. Identifies enforcement and awareness gaps in anti-poaching efforts. Recommends integrative conservation through law and community roles. Keywords: Legal Protection, Wildlife, Poaching, Conservation Law, Indonesia